PENYULUHAN PEMANFAATAN MEDIA DIGITAL UNTUK MENINGKATKAN KEMAMPUAN PROMOSI EDUWISATA DAN USAHA KELOMPOK TANI YURGA FARM - Salsalina Aprilia Br Ginting; Eunike Florentina Br Tarigan; Diana Intan Sari; Dwi Laila Maulida; Adi Candra (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
The use of digital media is a key strategy for promoting agricultural businesses and developing agritourism sustainably. The Yurga Farm Farmers’ Group has great potential as an agricultural agritourism destination, but its use of digital media for promotion remains limited. This community service activity aims to improve the farmers’ group members’ understanding and skills in utilizing digital media as an effective promotional tool. The methods employed included lectures, discussions, practical training, and mentoring focusing on digital marketing, social media management, branding, promotional content creation, and the use of the Canva application. Evaluation was conducted through pre- and post-tests involving 10 participants. The results showed an average increase in participants’ understanding of 13.7%. Significant improvements were observed across all indicators, particularly in the ability to use simple design applications. Participants were able to produce various digital promotional materials such as photos, videos, leaflets, catalogs, company profiles, and video profiles. This activity proved effective in enhancing the capacity of farmer group members to support edutourism promotion and sustainable agricultural business development. ABSTRAK Pemanfaatan media digital menjadi strategi penting dalam mendukung promosi usaha tani dan pengembangan eduwisata secara berkelanjutan. Kelompok Tani Yurga Farm memiliki potensi besar sebagai destinasi eduwisata pertanian, namun pemanfaatan media digital untuk kegiatan promosi masih sangat terbatas. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman serta keterampilan anggota kelompok tani dalam memanfaatkan media digital sebagai sarana promosi yang efektif. Metode pelaksanaan meliputi ceramah, diskusi, pelatihan praktik, dan pendampingan yang berfokus pada materi digital marketing, pengelolaan media sosial, branding, pembuatan konten, serta pengoperasian aplikasi Canva. Evaluasi dilakukan menggunakan metode pre-test dan post-test terhadap sepuluh orang peserta. Hasil menunjukkan bahwa terjadi peningkatan rata-rata pemahaman peserta sebesar 13,7%. Peningkatan signifikan tercatat pada seluruh indikator, terutama kemampuan penggunaan aplikasi desain sederhana. Peserta berhasil menghasilkan berbagai media promosi digital seperti foto, video, leaflet, katalog, company profile, dan video profile. Kegiatan pengabdian ini terbukti efektif dalam meningkatkan kapasitas anggota kelompok tani untuk mendukung promosi eduwisata dan pengembangan usaha tani lokal.